EFFECTIVENESS OF PROMOTIONAL MIX STRATEGIES IN A PRIVATE SENIOR HIGH SCHOOL: A CASE STUDY - Angelito Magbato Ebora (PT Wahana Global Education, 2026)
The concept of promotion involves various marketing communications, including publicity, public relations, and advertising, used to create awareness and persuade customers to purchase. In the context of educational institutions, schools have adopted promotional strategies to compete effectively, increase enrollment, and boost revenue. Bina Bahari Christian Senior High School has faced challenges in enrollment, which administrators attribute to external factors beyond their control. This study evaluates the effectiveness of promotional mix strategies in increasing student enrollment. The research focuses on promotional strategies such as advertising, public relations, sales promotion, direct marketing, school appearance, and publicity. It examines the perceptions of students, parents, and teachers regarding the effectiveness of these strategies in attracting students. A survey questionnaire was used to gather data from respondents, with random sampling for students and teachers, and purposive sampling for parents. Descriptive research design and quantitative methods were employed. The study revealed that promotional mix strategies were effective in attracting and retaining students. Advertising, public relations, sales promotions, direct marketing, school appearance, and publicity significantly influenced the level of enrollment. No significant differences were found in the perceptions of students, teachers, and parents regarding the effectiveness of these strategies. Regression analysis identified that these strategies predict a high level of student enrollment. The study concludes that using these promotional mix strategies effectively contributes to achieving a high level of enrollment in the school.